(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2023)
Due to the second-year financial accounting students’ subpar performance, this investigation was started. The aforementioned issue is brought on by students’ lack of enthusiasm for the study of financial accounting. It was discovered that the issue may be the result of subpar instruction, subpar student learning, and subpar subject interest. Every year, their low performance was repeated. Additionally, some of the students chose the business course because it was required of them by their parents or the school administration. Observing students’ behavior in financial accounting lectures and speaking with several of the pupils revealed the issue. Also, their performances in class exercises, class test, assignment and the end of term exams he gave them. The results of the class test showed the following results; 10 students representing 23% scored between 10 to 20 marks and 33 students representing 77% of the total population scored between 0 to 9 marks. The results of the end of first year third term examination showed the following result showed the following results; 0 students (0%) had A1, 3 students (7%) had between B2 and B3, 10 students (22%) had between C4 to C6, 5 students (12%) had D7, 20 students (47%) had E8 and 5 students (12%) had F9. The information gathered above showed that the form two business students of Afua Kobi Ampem Senior High School were performing very poorly in the area of Financial Accounting thus the need for this study.